(untitled) (Homoeopathy for All, 2022)
Hymenoptera is an order of insects including bees, wasps and ants characterized by locked pairs of membranous wings and high development of social or colonial behavior. Man had started the use of insects and insect products since ancient time. Hymenoptera deals with some important and very useful homoeopathic medicines like Apis mellifica, Formica rufa and Vespa crabro.